Design, Synthesis, enzyme inhibitory activity and molecular docking studies of new 1,2,3-triazole linked nucleobases - Aditya Aggarwal; Chanchal Vashisth; Komal Bharti; Neera Raghav; Surender Kumar (Results in Chemistry)
Thirteen novel 1,2,3-triazole linked nucleobases (5a-m) were designed and efficiently synthesized as potential human enzyme inhibitors. The target compounds were synthesized by using Copper (I)-catalysed Huisgen-Sharpless-Meldal 1,3-dipolar cycloaddition reaction of propargylated nucleobases and substituted aryl azides in good yield. Compounds (5a-m) were characterized by their 1HNMR, 13C NMR, 2D NMR and mass spectral data. All compounds were screened in vitro for their inhibitory efficacy against pepsin, trypsin, lipase and α-amylase enzymes. All the compounds showed more than 50 % inhibition against these enzymes. Interestingly, four compounds, including 5d, 5h, 5k and 5m displayed excellent potent level of enzyme inhibitory activity at 10−7 M concentration. Further, molecular docking analysis revealed that some compounds shown significant binding interactions with target sites. Compound 5h exhibited the highest enzyme inhibitory activity (trypsin, % inhibition = 81.55) at 10−7 M concentration in comparison to the reference drug orlistat.